An Innovative Technique to Prevent Air Leaks from Cervical Esophagostomy during Face Mask Ventilation - Shreya Shah; Prabudh Goel; Kanika Sharma; Teg Rabab Singh; Puneet Khanna; Rajeshwari Subramaniam; Vishesh Jain; Anjan Kumar Dhua; Devendra Kumar Yadav; Minu Bajpai; Sandeep Agarwala (Wolters Kluwer Medknow Publications, 2024)
During face mask ventilation, invariably, some air enters the esophagus rather than the airways; this results in gastric insufflation while the esophagus is intact or loss of tidal volume in patients with a cervical esophagostomy (Cx-esophagostomy). OBJECTIVE: The objective of the study was to report the indigenous use of an electrocardiography (ECG) electrode in successfully occluding the Cx-esophagostomy to prevent inadvertent loss of tidal volume. MATERIALS AND METHODS: Twenty-nine observations were recorded on 27 patients (mean age: 10.9 months; male:female = 2.6:1). The oral cavity, pharynx, and Cx-esophagostomy were cleared of saliva. Peristomal area was cleaned with dry gauze and dried with alcohol. Latex-free, 50 mm, ECG electrode was pasted symmetrically over the Cx-esophagostomy. The efficacy of the electrode was assessed using a five-point algorithm: (i) collapse of reservoir bag, (ii) chest expansion, (iii) ballooning of electrode, (iv) cotton-wisp test, and (v) change in compliance with manual compression of the electrode. Subgroup analysis was conducted for laterality and health of Cx-esophagostomy. Results: Study cohort: Cx-esophagostomy was located on the left in 58.26% (n = 17/29) patients. The health of Cx-esophagostomies was graded from I to IV (n = 9, 16, 3, and 1, respectively). The collapse of the reservoir bag and chest rise indicated successful ventilation. Ballooning of the electrode with each breath was observed in 79% (23/29) patients. Partial separation of the electrode from the skin (exaggerated with each breath) was observed in 10.3% (3/29) patients (Group I: n = 1, Group III: n = 1, and Group IV: n = 1). This was related to poor local preparation or pooling of saliva (n = 1; Group I: resolved with procedural re-application of a fresh electrode) and underlying skin condition (n = 2; Groups III and IV: resolved only temporarily with re-application). The cotton-wisp test was positive in two additional patients (1 each in Groups II and III) and was related to the pooling of saliva. No change in compliance was observed with manual compression of the electrode. No difference in success was observed between left and right Cx-esophagostomies. Overall success with this technique was 82.8% with a potential for 100% in those with peristomal health graded I-III. Conclusions: The ECG electrode is a technically simple, cost-effective, and widely available device, instrumental in addressing the problem of air leak through Cx-esophagostomy during face mask ventilation before intubation.